Methylene blue sustainability of root-tip protoplasts as an indicator of aluminum tolerance in a wide range of plant species, cultivars and lines - Wagatsuma, Tadao; Khan, Shahadat Hossain; Rao, Idupulapati M.; Wenzl, Peter; Tawaraya, Keitarou; Yamamoto, Takanori; Kawamura, Takeshi; Hosogoe, Kazumi; Ishikawa, Satoru (Informa UK Limited, 2005)
We previously developed a new simple technique of methylene blue (MB) staining for the discrimination of aluminum (Al)-tolerant protoplasts from 4 plant species (rice, oats, maize and pea). The objectives of the present study were to confirm the applicability of this technique to a wider range of plant species, cultivars and lines, and to identify a common strategy for the early stage of Al tolerance. A total of 10 plant species, two Brachiaria spp., two Oryza spp., buckwheat, maize, pea, triticale, wheat and barley, corresponding to 18 different plant samples (species, cultivars, and lines), were used. Al tolerance (relative net root elongation of the longest root), which was screened at 20 μM AICI3 in 0.2 mM CaCl2 (pH 4.9) for 24 h, ranged widely from 10 to 88. Among cultivars and lines within the same species, Al accumulation in the root tip portion was higher in Al-sensitive plants, corresponding to more severe permeabilization of the plasma membranes (PM). Protoplasts isolated mainly from the epidermis, and outer and central parts of the cortex were stained to different degrees by MB, and the blue color was observed both on the surface and inside the protoplasts. Color pictures obtained after staining for 3 min with 0.1% MB were analyzed by Image Hyper II. The ratio of the heavily stained area at threshold 95 to the entire area stained with MB at threshold 125 was defined as MB stainability. MB stainability was negatively correlated with Al tolerance (y= 48.6e−0.02x, R 2= 0.676**) suggesting the common importance of permeation characteristics of PM, in addition to PM negativity for Al tolerance in a wide range of plant species, cultivars and lines. Analysis of the PM lipid composition was proposed as an important topic for future studies on the negativity and permeation of PM.